Stratifin promotes the malignant progression of HCC via binding and hyperactivating AKT signaling - Li, Rong; Yan, Xijing; Zhong, Wenhui; Zheng, Jun; Li, Xuejiao; Liang, Jinliang; Hu, Zhongying; Liu, Huanyi; Chen, Guihua; Yang, Yang; Zhang, Jianwei; Qu, Enze; et al. (Cancer letters, 2024)
Hepatocellular carcinoma (HCC) is a highly aggressive malignant tumor with limited treatment options and poor prognosis. In this study, we reveal the pivotal role of Stratifin (SFN), also recognized as 14-3-3σ, in driving HCC progression. Our investigation underscores a substantial upregulation of SFN within HCC tissues, manifesting a significant association with worse prognostic outcomes among HCC patients. In vitro and in vivo experiments reveal that SFN overexpression significantly amplifies proliferation, mitigates sorafenib-induced effects on HCC cells, and enhances tumorigenesis. While SFN silencing exerts converse effects on HCC progression. Additionally, we unveil a critical interaction between SFN and AKT, where SFN boosts AKT kinase activity by disrupting the binding of PHLPP2 and AKT, thereby intensifying the malignant progression of HCC cells. In conclusion, this study identifies the oncogenic role of SFN and elucidates the regulatory mechanism of the SFN/AKT axis in HCC, which may provide valuable insights into the mechanisms of HCC progression and potential targets for therapeutic intervention. •SFN is elevated in HCC and is associated with the worse prognosis of patients.•SFN promotes HCC cell growth and resistance to sorafenib-induced cell death.•SFN interacts with AKT, enhancing AKT's kinase activity via blocking the binding of PHLPP2 and AKT.•SFN's ability to promote HCC progression depends on its regulation of AKT kinase activity.•SFN emerges as a potential therapeutic target and a promising prognostic marker for HCC.